Preparation method, product and application of porous carbon spherical shell nanoparticles
By coating polyacrylonitrile on the surface of alumina nanoparticles and preparing porous carbon spherical nanoparticles by physical denaturation method, the problems of pollution, complex operation and high cost in the prior art are solved, and high efficiency is achieved under normal temperature and pressure Preparation, suitable for a variety of application fields.
Patent Information
- Application Number
- CN202411290961.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-17
AI Technical Summary
The existing carbon spherical shell nanomaterial preparation technology has problems such as pollution, complex operation, expensive equipment and high cost, especially traditional template method, sol-gel method, chemical vapor deposition method and microwave-assisted heating method.
Polyacrylonitrile (PAN) solution was coated on the surface of alumina nanoparticles, and porous carbon spherical nanoparticles were formed under normal temperature and pressure by physical denaturation method. After that, the alumina template was removed and porous carbon spherical nanoparticles were obtained by drying and calcining. Granules.
It realizes batch continuous preparation of porous carbon spherical nanoparticles under normal temperature and pressure, avoids the influence of high temperature and high pressure and impurities, and is simple, flexible and reliable in operation, and is suitable for energy storage, drug preparation and environmental governance.
Smart Images

Figure CN119143115A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of new materials, and in particular to a preparation method, product and application of porous carbon spherical shell nanoparticles. Background Art
[0002] With the continuous development of science and technology, the uniqueness of carbon spherical shell materials has attracted people's attention and triggered the scientific and industrial communities to explore and utilize them more deeply. Researchers have found that by finely controlling the pore size, shell thickness and surface chemical properties of carbon spherical shells, their application range can be further expanded.
[0003] In the field of energy storage, carbon spherical shell materials have shown extraordinary potential. Their high specific surface area and excellent conductivity make them ideal electrode materials, which can significantly improve the energy density and cycle stability of batteries and supercapacitors. In addition, by introducing specific functional groups or nanoparticles, the electrochemical properties of carbon spherical shell materials can be further enhanced, providing strong support for the development of new and efficient energy storage devices.
[0004] In the biomedical field, carbon spherical shell materials also have broad application prospects. Their good biocompatibility and modifiability make them ideal candidate materials for drug delivery systems, biosensors, and tissue engineering. By precisely controlling the size and surface properties of carbon spherical shells, targeted delivery and sustained release of drugs can be achieved, improving therapeutic effects and reducing side effects.
[0005] In addition, carbon spherical shell materials also play an important role in environmental governance. Their high adsorption and selectivity enable them to effectively remove harmful substances such as heavy metal ions and organic pollutants in water, providing a powerful means for protecting water resources and improving environmental quality.
[0006] In summary, as a new type of material with multiple excellent properties, carbon spherical shell materials have shown broad application prospects in many fields such as energy, biomedicine, and environmental governance. With the continuous deepening of research and the continuous advancement of technology, it is believed that carbon spherical shell materials will play an important role in more fields and make greater contributions to the progress and development of human society.
[0007] At present, the preparation process of carbon spherical shell nanoparticles includes template method, which is a common method for preparing carbon spherical shell materials. The key lies in selecting and processing a suitable template. The template can be a hard template or a soft template such as a surfactant or a polymer; the sol-gel method is a method for preparing materials based on chemical reactions, which is also suitable for the preparation of carbon spherical shells; the chemical vapor deposition method (CVD) method is a method for directly depositing materials on a substrate through chemical reactions in the gas phase. For the preparation of carbon spherical shells, a carbon layer can be deposited on the surface of the template by CVD, and then a hollow structure is obtained by removing the template; the solvent (water) thermal method is a method of promoting chemical reactions in a closed reactor using a high temperature and high pressure solvent environment. For the preparation of carbon spherical shells, the solvent thermal method can directly generate a hollow structure through one or more steps of reaction. In addition to the above traditional preparation methods, some new preparation technologies and processes have emerged in recent years. For example, advanced technologies such as microwave assisted heating are used to prepare carbon spherical shell materials with special morphology and functions.
[0008] In summary, there are many methods and processes for preparing carbon spherical shell nanomaterials, and different methods are suitable for different application scenarios and performance requirements. With the continuous advancement and innovation of science and technology, it is believed that more novel and efficient preparation technologies and processes will be developed in the future.
[0009] The existing carbon spherical shell nanomaterial preparation technologies, whether it is the traditional template method, sol-gel method, chemical vapor deposition (CVD), solvent (hydro) thermal method, or microwave assisted heating method, all have serious defects. For example, the traditional template method uses strong acid and strong base to remove the template, which causes contamination. Some steps in the preparation process of the sol-gel method are difficult to control. The equipment required for the preparation of the chemical vapor deposition (CVD) method is usually expensive and complicated to operate. The solvent (hydro) thermal method and microwave assisted heating method also have problems such as complex operation, expensive and complex equipment, and high cost. Summary of the invention
[0010] Based on the above content, the present invention provides a preparation method, product and application of porous carbon spherical shell nanoparticles. The method of the present invention can continuously coat the carbon source on the surface of alumina nanoparticles in batches by physical denaturation at room temperature and pressure, remove the alumina nanoparticle template by immersion in water with stirring at room temperature, and finally obtain porous carbon spherical shell nanoparticles by drying and calcining.
[0011] To achieve the above object, the present invention provides the following solutions:
[0012] One of the technical solutions of the present invention is a method for preparing porous carbon spherical shell nanoparticles, comprising the following steps:
[0013] Add polyacrylonitrile into an organic solvent and dissolve it to obtain a PAN solution;
[0014] Adding aluminum oxide nanoparticles into the PAN solution and mixing well to obtain a mixed solution of aluminum oxide nanoparticles to be coated;
[0015] Adding the mixed solution of the aluminum oxide nanoparticles to be coated into water in the form of droplets to form composite nanoparticles, and then stirring to obtain PAN carbon source spherical shells;
[0016] The PAN carbon source spherical shell is dried, carbonized and sintered to obtain the porous carbon spherical shell nanoparticles.
[0017] The second technical solution of the present invention is a porous carbon spherical shell nanoparticle prepared by the above preparation method.
[0018] The third technical solution of the present invention is the application of the above-mentioned porous carbon spherical shell nanoparticles in the field of energy storage, drug preparation or environmental management.
[0019] The present invention discloses the following technical effects:
[0020] The present invention uses polyacrylonitrile (PAN) as a carbon source, and fully utilizes the characteristic of polyacrylonitrile undergoing physical denaturation when in contact with water to complete the coating of the carbon source on the nano-metal particles. During the spraying process, the mixed solution of the aluminum oxide nano-particles and PAN is dispersed into numerous small droplets of the PAN solution encapsulating the aluminum oxide nano-particles, and at the same time undergoes denaturation when in contact with water to complete the coating of the carbon source on the nano-metal particles. This process is only based on physical characteristics and does not involve factors such as high temperature, high pressure, and introduction of impurities, thereby avoiding affecting the inherent properties of the nano-metal particles.
[0021] The method of the present invention can be mass-produced and has high continuity. At the same time, the carbonization process can further set different carbonization temperatures and carbonization atmospheres according to specific carbonization requirements. It has the advantages of simple operation, flexibility and high reliability, and provides a new way for the preparation of porous carbon spherical shell nanoparticles. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0023] Figure 1 This is a scanning electron microscope image of the porous carbon spherical shell nanoparticles prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0024] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0025] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0026] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0027] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0028] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0029] The first aspect of the present invention provides a method for preparing porous carbon spherical shell nanoparticles, comprising the following steps:
[0030] Add polyacrylonitrile into an organic solvent and dissolve it to obtain a PAN solution;
[0031] Adding aluminum oxide nanoparticles into the PAN solution and mixing well to obtain a mixed solution of aluminum oxide nanoparticles to be coated;
[0032] Adding the mixed solution of the aluminum oxide nanoparticles to be coated into water in the form of droplets to form composite nanoparticles, and then stirring to obtain PAN carbon source spherical shells;
[0033] The PAN carbon source spherical shell is dried, carbonized and sintered to obtain the porous carbon spherical shell nanoparticles.
[0034] In practical applications, alumina nanoparticles can be replaced by other nanoparticles that can be dissolved in PAN solution.
[0035] In some embodiments of the present invention, the organic solvent is N,N-dimethylformamide;
[0036] The dissolution process is carried out under a sealed condition. The polyacrylonitrile is dissolved by stirring at 100 rpm to 800 rpm for 0.5 h to 6 h at a temperature of 30° C. to 80° C.
[0037] The molecular weight of the polyacrylonitrile is 50,000 to 250,000, and more preferably 200,000.
[0038] In some embodiments of the present invention, the concentration of the PAN solution is 0.03 g / ml to 6 g / ml, and more preferably 2 g / ml.
[0039] When the concentration of PAN solution is too high, the carbon source shell after coating will be thicker, which is not conducive to obtaining porous carbon shell spheres. When the concentration is too low, it is not easy to form a carbon source shell, and even if it is formed, the strength is low.
[0040] In some embodiments of the present invention, the mass ratio of the aluminum oxide nanoparticles to the polyacrylonitrile is 1:(0.5-30).
[0041] In some embodiments of the present invention, during the mixing process, stirring is performed at 100 rpm to 800 rpm for 0.5 h to 10 h at room temperature.
[0042] In some embodiments of the present invention, the stirring rate is 50 rpm to 1000 rpm, and the time is 1 h to 24 h; and the stirring is performed at room temperature.
[0043] In some specific embodiments, the mixed solution of the aluminum oxide nanoparticles to be coated can be sprayed into water to form composite nanoparticles by a spray coating process. Specifically, the concentric needle is first fixed on a rack and placed with the concentric needle facing downward, and then a syringe is used to extract the uniform mixed solution obtained in step 2 and fixed in an automatic propulsion device. The syringe head is connected to the outer channel of the concentric needle, and the inner channel of the concentric needle is connected to the air cylinder through a hose. A stirrable water tank is placed under the concentric needle. When the spraying starts, the air source is turned on first, and the automatic propulsion device is turned on after the air flow rate is stable. Under the action of the air flow, the mixed solution to be coated forms countless small droplets and is sprayed onto the water surface. The solution PAN is instantly modified and solidified into a solid phase when it meets water, and the PAN carbon source is coated on the surface of the nano-alumina particles, and finally composite nanoparticles are formed. Then the stirring is started to dissolve the nano-alumina particles. In the specific implementation case, the inner channel needle diameter of the concentric needle is 1 to 2 mm, and the outer diameter is 2 to 5 mm. The flow rate of the air cylinder source pressure reducing valve is 0.3-1.5Mpa, preferably 0.7Mpa, and the automatic propulsion speed of the syringe is 0.5-3ml·s -1 The preferred propulsion speed is 1.5 ml·s -1 , the diameter of the water tank is ≧1000mm, the stirring rate under the water tank is 50rpm~1000rpm, and the stirring time is 1h~24h at room temperature. The distance between the concentric needle and the water surface of the water tank is 100mm~400mm, and the preferred distance is 200mm.
[0044] In some embodiments of the present invention, the drying temperature is 30-100° C., preferably 80° C., the drying time is 12 h to 72 h, preferably 48 h. The drying is performed under vacuum conditions.
[0045] In some embodiments of the present invention, the temperature of the carbonization sintering is 400-1000° C., preferably 650° C. The carbonization is performed under an inert atmosphere.
[0046] The second aspect of the present invention provides porous carbon spherical shell nanoparticles prepared by the above preparation method.
[0047] The third aspect of the present invention provides an application of the above-mentioned porous carbon spherical shell nanoparticles in the field of energy storage, drug preparation or environmental management.
[0048] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.
[0049] The molecular weight of PAN used in the examples of the present invention is 200,000.
[0050] The particle size of the aluminum oxide nanoparticles used in the embodiment of the present invention is 50 nanometers.
[0051] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0052] Example 1
[0053] Step 1, preparation of PAN solution: Add polyacrylonitrile (PAN) reagent to N,N-dimethylformamide (DMF) reagent and seal it, and stir it at 60°C and 400 rpm for 3 h using a heated magnetic stirrer until PAN is completely dissolved in the DMF solvent to obtain a PAN solution with a mass concentration of 2 g / ml.
[0054] Step 2, preparation of a mixed solution of aluminum oxide nanoparticles to be coated: adding aluminum oxide nanoparticles to the above PAN solution and continuously stirring at 500 rpm for 3 hours to obtain a uniformly mixed mixed solution of aluminum oxide nanoparticles to be coated; wherein the mass ratio of aluminum oxide nanoparticles to PAN in the PAN solution is 1:20.
[0055] Step 3, implementation of the spray coating process: first fix the concentric needle on the rack and place the concentric needle head downward, then use a syringe to extract the mixed solution of the aluminum oxide nanoparticles to be coated obtained in step 2 and fix it in the automatic propulsion device, the syringe head is connected to the outer channel of the concentric needle, and the inner channel of the concentric needle is connected to the air cylinder through a hose, and a stirrable water tank is placed under the concentric needle. When the spraying starts, turn on the air source first, and then turn on the automatic propulsion device after the air flow rate is stable. Under the action of the air flow, the mixed solution of the aluminum oxide nanoparticles to be coated forms countless small droplets and is sprayed onto the water surface. The solution PAN is instantly modified and solidified into a solid phase when it meets water, and composite nanoparticles with PAN carbon source coated on the surface of nano-alumina particles are obtained. Then start stirring, dissolve the nano-alumina particles, and filter to obtain the PAN carbon source spherical shell. Among them, the inner channel needle diameter of the concentric needle is 1.63mm and the outer diameter is 2.77mm. The flow rate of the air cylinder source pressure reducing valve is 0.7Mpa, and the automatic propulsion speed of the syringe is 1.5ml·s -1 The diameter of the water tank is 1000 mm, the stirring rate under the water tank is 200 rpm, and the stirring is carried out for 1 hour at room temperature. The distance between the concentric needle and the water surface of the water tank is 200 mm.
[0056] Step 4, carbonization process: the PAN carbon source spherical shell obtained in step 3 is placed in a vacuum drying oven at 80°C for 48 hours. After drying, the nano-spherical shell particles are placed in an inert gas protection furnace at 650°C for carbonization sintering for 3 hours. The inert atmosphere is ordinary nitrogen, and porous carbon spherical shell nanoparticles are finally obtained.
[0057] The SEM images of the porous carbon spherical shell nanoparticles prepared in this example are shown in FIG. Figure 1 shown by Figure 1 It can be seen that the obtained carbon spherical shell is basically spherical and has holes.
[0058] The particle size distribution of the porous carbon spherical shell nanoparticles prepared in this example is mainly concentrated at 75 nanometers, and the shell thickness is 25 nanometers.
[0059] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing porous carbon spherical shell nanoparticles, characterized in that: The following steps are involved: Add polyacrylonitrile into an organic solvent and dissolve it to obtain a PAN solution; Adding aluminum oxide nanoparticles into the PAN solution and mixing well to obtain a mixed solution of aluminum oxide nanoparticles to be coated; Adding the mixed solution of the aluminum oxide nanoparticles to be coated into water in the form of droplets to form composite nanoparticles, and then stirring to obtain PAN carbon source spherical shells; The PAN carbon source spherical shell is dried, carbonized and sintered to obtain the porous carbon spherical shell nanoparticles.
2. The method for preparing porous carbon spherical shell nanoparticles according to claim 1, characterized in that: The organic solvent is N,N-dimethylformamide; The molecular weight of the polyacrylonitrile is 50,000 to 250,000.
3. The method for preparing porous carbon spherical shell nanoparticles according to claim 1, characterized in that: The concentration of the PAN solution is 0.03 g / ml to 6 g / ml.
4. The method for preparing porous carbon spherical shell nanoparticles according to claim 1, characterized in that: The mass ratio of the aluminum oxide nanoparticles to the polyacrylonitrile is 1:(0.5-30).
5. The method for preparing porous carbon spherical shell nanoparticles according to claim 1, characterized in that: The stirring speed is 50 rpm to 1000 rpm, and the stirring time is 1 h to 24 h.
6. The method for preparing porous carbon spherical shell nanoparticles according to claim 1, characterized in that: The drying temperature is 30-100° C. and the drying time is 12-72 hours.
7. The method for preparing porous carbon spherical shell nanoparticles according to claim 1, characterized in that: The temperature of the carbonization sintering is 400-1000°C.
8. Porous carbon spherical shell nanoparticles prepared according to the preparation method according to any one of claims 1 to 7.
9. Application of the porous carbon spherical shell nanoparticles as claimed in claim 8 in the field of energy storage, drug preparation or environmental management.
Citation Information
Patent Citations
Nitrogen-doped porous carbon material for lithium-air battery positive electrode
CN103855366A
Preparation method of nitrogen-doped nano porous carbon spheres
CN107188155A
Methods of preparing core-shell graphene / polyacrylonitrile-based carbon nanospheres
US20200392326A1
Cited By
Millimeter-scale uniformly-distributed honeycomb-shaped hole carbon sphere as well as preparation method and application thereof
CN120483069A
